A Synthesis of Reading Comprehension Interventions for Persons With Mild Intellectual Disability. (August 2019) - Shelton, Alexandra; Wexler, Jade; Silverman, Rebecca D.; Stapleton, Laura M.
The inclusion of individuals with intellectual disability (ID) in typical settings is increasing. To promote success in these settings, educators must support the reading comprehension of individuals with ID. Therefore, we conducted a synthesis of the extant research on reading comprehension interventions for individuals in the largest category of ID—mild ID—in Grades 4 through 12 and postsecondary programs. We review the methodological and intervention features of eight group-design studies and six single-case design studies published between January 2001 and December 2018. Findings from the 14 studies revealed inconsistent effects of single-component and multicomponent interventions on expository and narrative reading comprehension. However, medium to large positive effects were typically found from interventions using peer-mediated instruction and explicit strategy instruction. More rigorous research investigating the effects of reading comprehension interventions for individuals with mild ID using standardized measures is warranted. Practical implications and recommendations for future research are discussed.